Analisa Keuangan Penerapan Aplikasi Sistem Keuangan Desa (SISKEUDES) dengan Model Delone dan McLean - Rabi'ah; Nurul Adha Oktarini Saputri (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
The Village Financial System Application (SISKEUDES) is an application developed by the Financial and Development Supervisory Agency (BPKP) to improve village financial management. The research aims to determine the success of the SISKEUDES application in Banyuasin Village. This research uses the Delone and McLean concept which consists of six assessments: system quality, data quality, service quality, usage, user satisfaction, and benefits. Data collection was done by interview and observation. The analysis of the success of the DeLone and McLean models shows that information quality is quite good and system quality equires maintenance, the quality of service is very good and helps the surrounding community in accessing and knowing the transparency of village finances. The obstacles faced are insufficient human resources from the village head to the community, the network is not evenly distributed in each region, and there are people who have not been able to afford to buy internet quota to access the SISKEUDES application.